ANALISIS PENILAIAN KINERJA ORGANISASI DENGAN MENGGUNAKAN KONSEP BALANCED SCORECARD PADA PD. BPR BKK BANJARHARJO - Waskita, Jaka; Purwanto, Medi Tri (PERMANA, 2012)
This study aims to measure the performance of PD. BPR BKK Banjarharjo with alternative concepts of balanced scorecard (BSC) through four perspectives: financial, customer (customers), internal business process, and learning and growth. Data analysis in this study uses: (1) a quantitative analysis technique that describes the business efficiency of calculations such as ratios to the BSC concept in measuring the performance of PD. BPR BKK Banjarharjo, and (2) qualitative analysis, comparing the data obtained from interviews and questionnaires delivery to customers and employees to know the level of customer satisfaction and employee PD. BPR BKK Banjarharjo. The results showed that the measurement of the performance of these companies over the concept of the balanced scorecard performance measurement through four perspectives, namely: financial perspective, customer, internal business processes and learning and growth suggests that, in general PD. BPR BKK Banjarharjo has been running the business well. It is seen from: (1) financial perspective, where high levels of ROA in 2010 is 7.02 per cent and operating profit growth rate of 27.60 percent and 20.52 percent of the operating ratio. (2) the customer perspective, where the ability to attract new customers in 2010 amounted to 6.69 per cent, 99.45 per cent rate of retaining customers, the profitability of loans amounting to 25.66 percent, and 50.76 percent customer satisfaction. (3) internal business perspective, where the level of product sales in 2010 amounted to 14.21 per cent (no change), cycle effectiveness of 0.053 percent and non-performing loans amounted to only 0.40 percent. (4) The growth and learning perspective, where the rate of employee turnover in 2010 amounted to 2.38 percent, the productivity of each employee to contribute 2.38 percent, 57.74 percent employee satisfaction expressed strongly agree, the level of information system capabilities by 43.65 percent agreed and the level of motivation of employees 44.05 per cent strongly agreed with the current conditions. The results of the analysis showed that the balanced scorecard balanced scorecard concept to meet the financial and non-financial aspects as well as to create new strategies for the future. The implication of this study is PD. BPR BKK Banjarharjo can develop a performance by enhancing the financial and non-financial aspects that refer to the calculation of the performance appraisal with the concept of BSC. In addition it can also be a strategy that is relevant to the condition of the bank and seek new breakthroughs that are applied to strategic goals can be achieved. Keywords: Balanced Scorecard, Corporate Performance, Corporate Strategy.